Dance activity interventions targeting cognitive functioning in older adults with mild cognitive impairment: A meta-analysis - Yuan, Yuxin; Li, Xiaofen; Liu, Wanxu (Frontiers in Psychology, 2022)
Objectives: To comprehensively determine the effect of dance activities on the cognitive functions and its sub-domains of older adults with mild cognitive impairment (MCI). Methods: We obtained data from PubMed, Web of Science, EBSCO, China national knowledge infrastructure, Wanfang data, and VIP databases from 2017/01/01 to 2022/03/01. We included trials of older adults with MCI that underwent dance activity intervention and fulfilled the inclusion criteria. Two researchers independently assessed the quality of the study using the Cochrane risk of the bias assessment tool. Meta-analysis was performed when data were available, with further subgroup analysis, using Review Manager 5.4, and sensitivity analysis was performed using Stata software 15.1. Results: Search terms yielded 183 articles, of which 12 fulfilled the inclusion criteria. This included 7 high-quality studies and 5 medium-quality studies. A total of 820 older adults were analyzed. Results showed that dance activity had beneficial effects for global cognition [SMDMMSE = 0.65, 95% CIMMSE (0.20, 1.09), pMMSE = 0.004; SMDMoCA = 0.87, 95% CIMoCA (0.44, 1.29), pMoCA <0.0001], memory [SMD = 0.61, 95% CI (0.35, 0.88), p <0.00001], visuospatial function [SMD = −0.39, 95% CI (−0.60, −0.19), p = 0.0002], cognitive flexibility [SMD = −0.31, 95% CI (−0.52, −0.11), p = 0.003], attention [SMD = 0.34, 95% CI (0.07, 0.61), p = 0.01], and balance [SMD = 1.25, 95% CI (0.06, 2.44), p = 0.04]. Further subgroup analysis showed that open-skill dance activity (OSDA) was more effective in promoting global cognition in older adults with MCI than closed-skill dance activity (CSDA) because of the different stimulation provided by the two types of dance activities in the brain regions of the older adults (p = 0.0002). It could be speculated that dance activity improved cognitive function mainly by affecting the microstructure and function of the cingulate tract, hippocampus, cardiovascular function, and other brain areas of older adults with MCI. Conclusions: Dance activities can significantly improve global cognition, memory, visuospatial function, cognitive flexibility, attention, and balance in older adults with MCI. However, more trials with rigorous study designs are necessary to provide more concrete evidence in the future.